Plant-made polio type 3 stabilized VLPs—a candidate synthetic polio vaccine - Johanna Marsian (Nature Portfolio, 2017)
Despite the success of current vaccination against poliomyelitis, safe, cheap and effective vaccines remain sought for continuing eradication effort. Here the authors use plants to express stabilized virus-like particles of type 3 poliovirus that can induce a protective immune response in mice transgenic for the human poliovirus receptor.